Forever indebted a real Mondrian or a clever fake - Vloten, Francisca van 1950- (De Factory, 2023)
No. 1 of the ICEAC Book Series entails the thoroughgoing research for a real or fake painting by Piet Mondrian. On Saturday. The painting was unearthed in the UK. Includes: - Report Herman van Putten, restorer of paintings (initial findings) - Report Cultural Heritage Agency of the Netherlands (overviews)
Keywords: Crabb, Hannah -- 1861-XXXX; Mondrian, Piet -- 1872-1944; Mondrian, Piet -- 1872-1944 -- London embankment; Echtheit; Zuschreibung